Consideration of Therapeutic Plasma Exchange in Association With Inflammatory Lesions in ANCA-Associated Glomerulonephritis: A Real-World Retrospective Study From a Single Center - Tampe, Désirée; Ströbel, Philipp; Korsten, Peter; Hakroush, Samy; Tampe, Björn (Frontiers in Immunology, 2021)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic vasculitis, most frequently presenting as microscopic polyangiitis (MPA) or granulomatosis with polyangiitis (GPA). Pathogenic ANCAs trigger a deleterious immune response resulting in pauci-immune necrotizing and crescentic glomerulonephritis (GN). Standard therapeutical regimens include aggressive immunosuppressive therapy. Since some patients require renal replacement therapy (RRT) despite intensive immunosuppressive therapy, additional therapeutic plasma exchange (PEX) to deplete pathogenic ANCAs has been recommended but its value has recently been questioned. Because therapeutic decision making is crucial in these critically ill patients, we here aimed to identify inflammatory lesions in association with PEX consideration in a retrospective study from a single center tertiary hospital in a real-world population of 46 patients with severe AAV requiring intensive care treatment. The decision to consider PEX was more likely in patients with need for intensive care treatment and severe renal dysfunction. In contrast, short-term outcomes did not depend on clinical or laboratory characteristics assessed at admission. Histopathological analysis confirmed active disease reflected by increased glomerular necrosis and crescents, but these histopathological findings did not associate with short-term outcome either. Interestingly, only increased global glomerular sclerosis in renal biopsies associated with a detrimental short-term outcome. In conclusion, our study investigated determinants for the consideration of therapeutic PEX in patients with severe AAV requiring intensive care treatment. This aspect underscores the need for renal biopsy and requires further investigation in a prospective controlled setting for therapeutic decision making especially in patients with severe AAV requiring intensive care treatment, especially important for treating intensivists.